FORMATION OF INTERCULTURAL COMPETENCE OF LEARNERS IN THE EDUCATIONAL PROCESS (Spectrum Journal of Innovation, Reforms and Development, 2023)
This article provides methodological recommendations for improving the content of literary education in the formation of intercultural competence of students, patriotic, international feelings, respect for traditions and spiritual and aesthetic heritage of different peoples and civilizations.